1972
DOI: 10.1139/b72-190
|View full text |Cite
|
Sign up to set email alerts
|

A correlation of nuclear DNA content and thin-layer chromatographic patterns in resolving genome relationships in Avena

Abstract: Relative amounts of nuclear deoxyribonucleic acid (DNA) from telophase root tip nuclei and thin-layer chromatographic patterns of alcohol-soluble compounds from dry leaves were determined for seven diploids: Avena clauda, A. pilosa, A. ventricosa, A. strigosa, A. hirtula, A. wiestii, A. longiglumis; four tetraploids: A. barbata, A. magna, A. abyssinica, A. vaviloviana; and four hexaploids: A. sterilis, A. fatua, A. byzantina, and A. sativa, in order to elucidate species relationships. Variation in nuclear DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

1973
1973
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…Based on averages within the A and C genome diploids, the difference in size is approximately 15%. This difference was also observed by Iiyama and Grant (1972), although the large variation among A genomes reported by these authors made this difference less striking, and the average difference that they reported was closer to 10%. The apparent divergence between the A and C sub-genomes is supported by previous studies showing major cytogenetic differences between A and C genome chromosomes that are most likely due to differences in repetitive DNA content (Fominaya et al 1988;Linares et al 1992;Jellen et al 1993).…”
Section: Interspecific Variation In Genome Sizesupporting
confidence: 52%
See 2 more Smart Citations
“…Based on averages within the A and C genome diploids, the difference in size is approximately 15%. This difference was also observed by Iiyama and Grant (1972), although the large variation among A genomes reported by these authors made this difference less striking, and the average difference that they reported was closer to 10%. The apparent divergence between the A and C sub-genomes is supported by previous studies showing major cytogenetic differences between A and C genome chromosomes that are most likely due to differences in repetitive DNA content (Fominaya et al 1988;Linares et al 1992;Jellen et al 1993).…”
Section: Interspecific Variation In Genome Sizesupporting
confidence: 52%
“…An alternate (or additional) explanation could be that the unknown B and D genomes are actually smaller than the observed A genomes. The hypothesis that the B genome is smaller than the A genome was put forward by Iiyama and Grant (1972) for this reason, although this was also in support of a proposed AABBDD genome constitution for the hexaploid, which has been subsequently rejected. Polyploid genome downsizing has been observed in most angiosperms, and it is assumed to be a general trend (Kellogg and Bennetzen 2004;Pellicer et al 2010a).…”
Section: Genome Size Reduction After Polyploidizationmentioning
confidence: 99%
See 1 more Smart Citation
“…3, 16 and 32 characterise the profiles of the hybrid taxon. These results are similar to those obtained by Alston and Turner (1962) in Baptisia, Iiyama and Grant (1972) in Avena, Murray and Williams (1973) in Briza media, and Kohli and Denford (1977) in Potentilla. Origin of new compounds through hybridity can be explained on the basis of new gene combinations leading to novel expression.…”
Section: Discussionsupporting
confidence: 90%